MATHEMATICAL MODELING OF DENTITION IN COMPLETE DENTURES - Donat V. Lola; Anton S. Nazarov (Вестник Северо-Кавказского федерального университета, 2022)
The article focuses on the development of a mathematical model for designing dentition in different types of the ration between the interalveolar arcs and the degree of atrophy in the alveolar processes of edentulous jaws.